2014
DOI: 10.4038/sljastats.v15i1.6792
|View full text |Cite
|
Sign up to set email alerts
|

On Comparison of Some Ridge Parameters in Ridge Regression

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Dorugade [5] introduced a Modified Two-Parameter (MTP) estimator, which was earlier defined in equation (7)…”
Section: The New Estimator and Its Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dorugade [5] introduced a Modified Two-Parameter (MTP) estimator, which was earlier defined in equation (7)…”
Section: The New Estimator and Its Propertiesmentioning
confidence: 99%
“…where 0 < d < 1. Dorugade [5] and Dorugade [6] introduced a modified two-parameter estimator. The estimator is given as:…”
Section: Introductionmentioning
confidence: 99%
“…Macedo [33] has improved the ridge-GME parameter estimator, which combines ridge regression and generalized maximum entropy to eliminate the subjectivity in the analysis of the ridge trace. Lukman et al [34] classify the estimators based on Dorugade [14] into different forms. They also provide some new ridge estimators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the presence of collinearity problem, the well-know ridge regression estimators are proposed (Hoerl and Kennard, 1970). There are many studies in the literature that focus on ridge regression (Dorugade, 2014). Moreover, studies have suggested the use of robust and ridge-type robust estimators if there are outliers, or both collinearity and outliers, in the regression data (Aftab and Chand, 2018;Alshqaq, 2021;Maronna, 2011;Silvapulle, 1991).…”
Section: Introductionmentioning
confidence: 99%